Worship and the New Cosmology : Liturgical and Theological Challenges - Vincie, Catherine, 1951- (Book collections on Project MUSE., 2014)
What is the Christian response to developments in the hard sciences? What do discoveries at the macro and micro levels have to say about Christian theology, about a theology of God, Christology, pneumatology, and creation? How do the developments in systematic theology that do take the advances in cosmology and the New Sciences seriously come to bear on our worship life? These are the questions addressed in Worship and the New Cosmology. It seeks to bring cosmology and the New Sciences into dialogue with developments in systematic and sacramental theology. This book also suggests some ways in which these developments might appear in our worship. Catherine Vincie's study seeks to reduce the cognitive dissonance between our scientifically informed everyday lives and our life of faith. (Publisher).